Study of Thermo-electronic Characteristics of Woven Heating Fabrics Embed with Silver Filaments Based on Infrared Images (Journal of Fiber Bioengineering and Informatics, 2016)
In the paper, two kinds of Woven Heated Fabrics (WHFs) were prepared and evaluated. WHFs werefabricated by integrated silver filaments into fabrics with the same interval distance, and silver paste wascoated on the crossing points of some WHFs to decrease contact resistance. Subsequently, surface infraredtemperature images and temperature simulated by finite element method were utilized to evaluatethe performance of WHFs. Experimental results showed surface temperature of WHFs is non-linearcorrelation with time when voltage was loaded on two ends of WHFs, but the surface equilibriumtemperature of WHFs is linear correlation with loaded voltage and power consumption. However,simulated surface temperature is highly consistent with the measured surface temperature of silverfilaments by adjusting the Heat Transfer Convection Coefficient (HTCC) at different loaded voltage.WHFs have wide application prospect in Electric Heating Garment (EHG) in the future. Infraredtemperature images and finite element simulation can decrease the cost and enhance design efficiency ofWHFs.
Keywords: Active Warming; Thermo-electronic Behavior; Woven Heating Fabric; Infrared Temperature Image; Silver Filament